Echocardiographic assessment of ventricular function: Conventional and advanced technologies and their clinical applications. (September 2020) - Tsuda, Takeshi; Kernizan, Daphney; Del Grippo, Erica; Thacker, Deepika; Kharouf, Rami; Srivastava, Shubhika
Abstract: Echocardiogram is the first-line and most used noninvasive imaging diagnostic modality and is convenient and reliable in its assessment of ventricular function in pediatrics. Ventricular function is an important physiological parameter representing myocardial performance in response to overall hemodynamic status. Here, we introduce basic principles of conventional echocardiography and advanced echocardiographic technology, including tissue Doppler imaging, 3-dimensional echocardiogram, and speckled tracking echocardiography. Then, we overview clinical applications of these methods in assessing ventricular function in pediatrics, including single ventricle after staged surgical palliation, right ventricular dysfunction in pulmonary hypertension, and ventricular-ventricular interactions in various heart disease. With multimodality approaches, the advantages and limitations of echocardiographic assessment of ventricular function are discussed. Highlights: Assessment of ventricular function is an integral part of cardiology practice. Advanced echocardiographic technology provides significant physiological data. Speckle tracking echocardiography is a promising new diagnostic modality. Multimodality approach is warranted for complex cardiac problems in children.